Negative pole piece, secondary battery and electric device

By using carbon microspheres with porous three-dimensional structure as conductive agent in the negative electrode sheet of the power battery, the unstable battery pack structure and vehicle safety problems caused by the expansion of the negative electrode sheet are solved, and higher battery cycle life and safety are achieved.

CN119852404APending Publication Date: 2025-04-18ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411997458.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

During the circulation process, existing power batteries swell due to the expansion of the negative electrode plate and gas production, which affects the structural reliability of the battery pack and the safety of the entire vehicle.

Method used

Carbon microspheres composed of layered carbon nanosheets are used as conductive agents, and the expansion of the electrode sheet is reduced through their porous three-dimensional structure and hollow nanocage structure, and the density of the conductive network and the liquid retention ability of the electrode sheet are improved.

Benefits of technology

Effectively alleviate the expansion of the negative electrode plate, absorb expansion stress, improve the stability of the electrode plate and battery cycle life, while reducing the expansion risk of the battery pack and enhancing the safety of the whole vehicle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852404A_ABST
    Figure CN119852404A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a negative pole piece, a secondary battery and an electric device. The negative pole piece comprises a negative active material, a binder and a conductive agent, the conductive agent comprises carbon microspheres, the carbon microspheres are composed of layered carbon nanosheets, the carbon nanosheets are composed of carbon nanocages, and the carbon nanocages have a porous three-dimensional structure. In the invention, a space is formed between the carbon nanosheets of the carbon microspheres, and the nanocage is of a hollow structure, so that when the negative electrode material is expanded and the carbon nanospheres are extruded, the expansion of the pole piece can be effectively relieved, meanwhile, the stress generated based on the expansion of the negative electrode material is absorbed, and the stability of the pole piece is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to a negative electrode sheet, a secondary battery and an electrical device. Background Art

[0002] With the rapid development and widespread application of long-range electric vehicles, long-range electronic products, power tools, etc. in the new energy field, the life of power batteries is becoming more and more important. However, for existing power batteries, the negative electrode plate will swell and produce gas during the cycle, which will affect the structural reliability of the battery pack and bring safety problems to the whole vehicle. Therefore, it is necessary to improve the cycle performance and safety of the corresponding power batteries. Summary of the invention

[0003] The present application provides a negative electrode plate, the design of which can reduce the expansion of the negative electrode plate, further reduce the expansion of the power battery, and thus improve the reliability and safety of the battery pack.

[0004] Some embodiments of the present application provide a negative electrode sheet, including: a negative electrode active material, a binder and a conductive agent, wherein the conductive agent includes carbon microspheres, the carbon microspheres are composed of layered carbon nanosheets, the carbon nanosheets are composed of carbon nanocages, and the carbon nanocages have a porous three-dimensional structure. In some embodiments, the specific surface area of ​​the carbon microspheres is ≥1100m 2 / g, optionally, 1100m 2 / g-1500m 2 In this application, the carbon microspheres have a large specific surface area (≥1100m 2 / g), when it is used as a conductive agent, the conductive network formed in the pole piece is denser and the negative pole piece resistance is smaller when the amount is the same as that of ordinary conductive agents. In addition, the carbon nanocage structure inside the carbon microsphere can be filled with electrolyte, which can provide more ion transmission channels during the cycle process, greatly improve the battery cycle life, and improve the pole piece's ability to retain liquid. In addition, there is space between the carbon nanosheets of the carbon microsphere, and the nanocage is a hollow structure. When the negative electrode material expands, the carbon nanosphere is squeezed, which can effectively alleviate the expansion of the pole piece, while absorbing the stress generated by the expansion of the negative electrode material, and improving the stability of the pole piece.

[0005] In some embodiments, the size of the carbon nano cage is 10nm-20nm, and further, the size is the maximum size of the carbon nano cage in the three-dimensional direction, that is, the size is the length of the carbon nano cage. Further, the thickness of the carbon nano sheet (petal) is ≤100nm. In the present application, when the size of the carbon nano cage is in this range (10nm-20nm), the shape of the carbon nano sheet (such as petal shape) composed of it can be better, and combined with the thickness of the carbon nano sheet (petal) ≤100nm, the specific surface area of ​​the carbon micron ball formed thereafter can be larger, thereby improving the performance of the battery. In addition, there is a certain space between adjacent carbon nano sheets, which can provide a certain buffering effect, and the nano cage is a hollow structure. When the negative electrode material expands, the carbon nano ball is squeezed, which can effectively alleviate the expansion of the pole piece.

[0006] In addition, the carbon nanosheet has a petal shape formed by the agglomeration of carbon nanocages, that is, the carbon nanosheet can be a petal, and the petals agglomerate to form a carbon micron flower of a carbon micron ball. Further, the particle size of the carbon micron ball is 2μm-10μm. In the present application, the petal-shaped carbon nanosheets agglomerate to form a carbon micron flower of a carbon micron ball, and the particle size of the carbon micron ball is 2μm-10μm, which can make the carbon micron ball have better dispersibility when used as a conductive agent, so that the conductive network formed in the formed negative electrode plate is denser.

[0007] In some embodiments, the negative electrode active material includes carbon and / or silicon negative electrode materials, wherein the carbon negative electrode material can be natural graphite, artificial graphite, soft carbon, hard carbon, etc.; silicon negative electrode materials such as elemental silicon, silicon oxide compounds (SiOx, x∈【0,2】), silicon carbon compounds (which may include porous carbon materials, and Si attached to the inside and / or surface of porous carbon materials), etc. Further, based on the total mass of the negative electrode sheet, the mass fraction of the negative electrode active material is 90%-99% (optionally 95%-98%), the mass fraction of the binder is 1%-4%, and the mass fraction of the conductive agent is 0.01%-10% (optionally 0.01%-1%). In the present application, carbon microspheres are used instead of traditional conductive carbon to act as an electronic conductive network, and the slurry is applied to copper foil to synthesize a new type of negative electrode sheet.

[0008] In some embodiments, the binder includes one or more of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC-Na), and in some other embodiments, other binders can be selected as needed.

[0009] Other embodiments of the present application provide a method for preparing the above-mentioned carbon microspheres of the conductive agent for the negative electrode plate, comprising: heating the metal salt to above the first temperature in an inert atmosphere; adding an organic carbon source, keeping warm for a first time, to obtain a carbon-coated metal oxide; removing the metal oxide to obtain the carbon microspheres, wherein the first temperature is 800°C ± 50°C. In some embodiments, the metal salt includes one or more of magnesium carbonate, zinc carbonate and iron carbonate, and the organic carbon source includes one or more of benzene, thiophene, pyridine, xylene and pyrimidine. In some embodiments, the first time is more than 1 hour. In some embodiments, the amount of the organic carbon source added relative to the metal salt is: 40μL / g-100μL / g.

[0010] In addition, embodiments of the present application also provide a secondary battery and a corresponding electrical device.

[0011] In summary, there is space between the carbon nanosheets of the carbon microspheres provided in the present application, and the nanocage is a hollow structure. When the negative electrode material expands, the carbon nanospheres are squeezed, which can effectively alleviate the expansion of the electrode sheet and absorb the stress generated by the expansion of the negative electrode material, thereby improving the stability of the electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0012]

[0013] The corresponding aspects of the embodiments of the present disclosure are best understood from the following detailed description when read in conjunction with the accompanying drawings.

[0013] Figure 1 A scanning electron microscope image of the carbon microsphere 100 at 10K magnification is shown.

[0014] Figure 2 An enlarged view of the carbon nanosheet 101 is shown.

[0015] Figure 3 The capacity retention rates of Example 1 and Comparative Example 1 are shown respectively.

[0016] Figure 4 The capacity retention rates of Example 2 and Comparative Example 2 are shown respectively. DETAILED DESCRIPTION

[0017] The applicant found that the carbon nanosheets of the carbon microspheres form petals, with space between the "petals", and the nanocage is a hollow structure (with many holes inside). When the negative electrode material expands, the carbon microspheres are squeezed, which can effectively alleviate the expansion of the pole piece, and absorb the stress generated by the expansion of the negative electrode material, thereby improving the stability of the pole piece. In addition, the carbon microspheres have a large specific surface area. When used as a conductive agent, the conductive network formed in the pole piece is more dense and the negative electrode pole piece resistance is smaller when the carbon microspheres are used in the same amount as ordinary conductive agents. In addition, the carbon nanocage structure inside the carbon microspheres can be filled with electrolyte, which can provide more ion transmission channels during the cycle process, greatly improving the cycle life of lithium iron phosphate batteries, and can improve the pole piece's ability to retain liquid.

[0018] Some embodiments of the present application provide a negative electrode sheet, including: a negative electrode active material, a binder and a conductive agent, wherein the conductive agent includes carbon microspheres, the carbon microspheres are composed of layered carbon nanosheets, the carbon nanosheets are composed of carbon nanocages, the carbon nanocages have a porous three-dimensional structure, wherein the specific surface area of ​​the carbon microspheres is ≥1100m 2 / g, optionally 1100m 2 / g-1500m 2 In this application, the carbon microspheres have a large specific surface area (≥1100m 2 / g), when it is used as a conductive agent, the conductive network formed in the pole piece is denser and the negative pole piece resistance is smaller when the amount is the same as that of ordinary conductive agents. In addition, the carbon nanocage structure inside the carbon microsphere can be filled with electrolyte, which can provide more ion transmission channels during the cycle process, greatly improve the battery cycle life, and improve the pole piece's ability to retain liquid. In addition, there is space between the carbon nanosheets of the carbon microsphere, and the nanocage is a hollow structure. When the negative electrode material expands, the carbon nanosphere is squeezed, which can effectively alleviate the expansion of the pole piece, while absorbing the stress generated by the expansion of the negative electrode material, and improving the stability of the pole piece.

[0019] In some embodiments, the size of the carbon nanocage is 10nm-20nm, and the size is the maximum size of the carbon nanocage in the three-dimensional direction, that is, the size is the length of the carbon nanocage. Further, the thickness of the carbon nanosheet (petal) is ≤100nm. In the present application, when the size of the carbon nanocage is in this range (10nm-20nm), the shape of the carbon nanosheet composed thereof (such as petal shape) can be better.

[0020] In addition, in the embodiments provided in the present application, the carbon nanosheets have a petal shape formed by the agglomeration of carbon nanocages, that is, the carbon nanosheets can be petals, and there are petals agglomerated to form carbon micron flower-shaped carbon micron balls. Optionally, the particle size of the carbon micron balls is 2μm-10μm. In the embodiments provided in the present application, petal-shaped carbon nanosheets agglomerate to form carbon micron balls, and the particle size of the carbon micron balls is 2μm-10μm, which is used as a conductive agent for the negative electrode of the secondary battery, which can effectively improve the dispersion of the carbon micron balls in the electrode and form a dense conductive network, and the carbon micron balls composed of petal-shaped carbon nanosheets have a large specific surface area, and there is a certain space / gap between adjacent carbon nanosheets of the carbon micron balls, so that the carbon micron flower-like structure can have a certain buffering effect when the electrode expands or contracts, thereby improving the stability of the carbon micron balls themselves, the conductive network and the electrode structure. Furthermore, the carbon microspheres, as a conductive agent, form a dense conductive network in the negative electrode plate, which is also beneficial for the electrolyte to infiltrate the plate, thereby improving the liquid retention of the plate and thus improving the electron and ion conductivity of the negative electrode plate.

[0021] In some embodiments, the negative electrode active material includes carbon and / or silicon negative electrode materials, wherein the carbon negative electrode material can be natural graphite, artificial graphite, soft carbon, hard carbon, etc.; silicon negative electrode materials such as elemental silicon, silicon oxide compounds (SiOx,, x∈【0,2】), silicon carbon compounds (may include porous carbon materials, and Si attached to the inside and / or surface of porous carbon materials), etc. In some embodiments, the negative electrode active material may include lithium titanate, etc. Optionally, the negative electrode active material includes one or more of natural graphite, artificial graphite, soft carbon, and hard carbon. Further, based on the total mass of the negative electrode sheet, the mass fraction of the negative electrode active material is 90%-99% (optionally 95%-98%), the mass fraction of the binder is 1%-4%, and the mass fraction of the conductive agent is 0.01%-10% (optionally 0.01%-1%). In the present application, carbon microspheres are used instead of traditional conductive carbon to act as an electronic conductive network.

[0022] In some embodiments, the binder includes one or more of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC-Na), and in some other embodiments, other binders can be selected according to requirements. In addition, the negative electrode conductive agent can also include one or a combination of two or more of conductive carbon black, nano silver powder, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc.

[0023] In addition, the present application also provides a method for preparing carbon microspheres of a conductive agent for a negative electrode plate, the method comprising: heating a metal salt to a first temperature or higher in an inert atmosphere; adding an organic carbon source, keeping the temperature for a first time, and obtaining a carbon-coated metal oxide; removing the metal oxide to obtain a carbon microsphere, wherein the first temperature is 800°C ± 50°C. In some embodiments, the metal salt includes one or more of magnesium carbonate, zinc carbonate, and iron carbonate, and the organic carbon source includes one or more of benzene, thiophene, pyridine, xylene, and pyrimidine. In some embodiments, the first time is more than 1h. In some embodiments, the amount of organic carbon source added relative to the metal salt is: 40μL / g-100μL / g. When the amount of organic carbon source is small, it may not be enough to coat the corresponding metal oxide, thereby reducing the specific surface area of ​​the carbon microspheres formed thereafter. When the amount of organic carbon source is too large, it may cause excessive carbon coating, thereby reducing the voids therein, thereby reducing the specific surface area of ​​the carbon microspheres formed thereafter. Specifically, basic magnesium carbonate is heated to above the first temperature in an inert atmosphere; organic carbon source benzene is added to basic magnesium carbonate, and the temperature is kept for more than 1 hour to obtain a carbon-coated magnesium oxide material, and magnesium oxide is removed to obtain the above-mentioned carbon microspheres. In the present application, basic magnesium carbonate is heated to above the first temperature in an inert atmosphere to ensure the subsequent carbonization of the organic carbon source. When the temperature is above the first temperature, if the temperature is too high (such as above 1000) / too low (such as below 750°C), the degree of graphitization (or conductivity) of the organic carbon source will be reduced, and the temperature is too low to affect the coating effect of the organic carbon source. The reaction involved in magnesium carbonate is: MgCO3→MgO+CO2↑. In some embodiments, the insulation time is more than 1 hour, which can ensure the full carbonization of the organic carbon source.

[0024] Specifically, the present application provides the following preparation method of carbon microspheres (taking magnesium carbonate as an example):

[0025] 1. MgO@C (carbon-coated magnesium oxide) was prepared by in-situ magnesium oxide template method at 800°C.

[0026] Basic magnesium carbonate (5 g) was placed in a quartz tube in a vertical furnace and heated at 8 °C min -1 -12℃min -1 (Optionally, at 10°C min -1 ) rate to above the first temperature, and the syringe pump was used to increase the temperature at 50 μL min -1 or more (optionally, 10 μL min -1 -60μL min -1) and inject 300 μL (optionally 200 μL-500 μL) of benzene at a feeding rate of 100 μL / min, keep the temperature for more than 1 hour, and cool naturally to room temperature in an Ar gas flow to obtain a mesostructured MgO@C. In some embodiments, the temperature is raised to above the first temperature to ensure the subsequent carbonization of the organic carbon source and the corresponding coating performance, but the temperature cannot be too high, such as above 1000°C, which will reduce the conductivity of the carbon microspheres prepared later.

[0027] 2. Use 6 mol L -1 HCl (any suitable concentration can be used according to the actual situation) is used to remove MgO, washed with ultrapure water for multiple times until neutral, and freeze-dried to obtain hierarchical carbon microspheres. In some embodiments, a smaller concentration such as 1 mol L -1 Of HCl, just remove the MgO.

[0028] The embodiments of the present application also provide a secondary battery and a corresponding power-consuming device, wherein the secondary battery may be a non-aqueous electrolyte lithium battery or a solid-state lithium battery. Taking a non-aqueous electrolyte lithium battery as an example, it includes a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.

[0029] Specifically, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector is, for example, a copper foil. The negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector. The negative electrode active material layer includes the above-mentioned negative electrode active material. The negative electrode conductive agent includes carbon microspheres. The negative electrode binder can be selected from conventional material types in the art, and no specific restrictions are made here. The mass fraction of the negative electrode active material is 90%-99% (optionally 95%-98%), the mass fraction of the binder is 1%-4%, and the mass fraction of the conductive agent is 0.01%-10% (optionally 0.01%-1%), and the conductive agent includes carbon microspheres. In the present application, carbon microspheres are used instead of traditional conductive carbon to act as an electronic conductive network.

[0030] The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side of the surface of the positive current collector. The positive current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam, etc. Among them, the thickness of the positive current collector is, for example, 8μm to 15μm. In this embodiment, the positive current collector is, for example, aluminum foil, and the thickness of the aluminum foil is, for example, 13μm. The positive current collector has two oppositely disposed surfaces along its own thickness direction, and the positive active material layer can be disposed on the surface of any one side thereof, or on both surfaces. The positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder, wherein the positive electrode active material includes lithium iron phosphate (LiFePO4), lithium cobaltate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganate, lithium cobaltate, lithium nickel manganese oxide, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium titanate and lithium-rich manganese-based materials. In some embodiments, the binder includes one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene, polyacrylate, sodium carboxymethyl cellulose, styrene-butadiene rubber and polyurethane, and optionally, the binder is vinylidene fluoride (PVDF). In the present application, carbon microspheres are used as conductive agents to improve the conductivity of the positive electrode sheet, such as for lithium iron phosphate positive electrode formula, which can greatly improve the conductivity of the positive electrode sheet of the battery. In addition, the specific formula can be selected by those skilled in the art according to actual needs.

[0031] The diaphragm is arranged between the positive electrode and the negative electrode to play an isolating role. The diaphragm can be, for example, a polyethylene film (PE), a polypropylene film (PP), a glass fiber film, a polyethylene film or a composite film. The thickness of the diaphragm is 9 to 18 μm, the air permeability is 180 s / 100 mL to 380 s / 100 mL, and the porosity is 30% to 50%.

[0032] The electrolyte infiltrates the positive electrode sheet and the negative electrode sheet. During the battery charging and discharging process, lithium ions are inserted and removed back and forth between the positive electrode sheet and the negative electrode sheet, and the electrolyte plays a role in conducting lithium ions. The electrolyte can be selected from conventional combinations in the art.

[0033] In one embodiment, the electrolyte includes an organic solvent and a lithium salt, wherein the organic solvent may be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), etc. The lithium salt may be selected from one of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalatophosphate), LiTFOP (lithium tetrafluorooxalatophosphate), or a combination thereof in any proportion. The molar concentration of the lithium salt in the electrolyte is 0.5 mol / L to 2 mol / L.

[0034] In other embodiments, some film-forming additives and functional additives that can improve battery performance may be added to the electrolyte, such as vinylene carbonate (VC), 1,3-propane sultone (PS), diethylene sulfate (DTD), etc. Those skilled in the art may select according to actual needs.

[0035] The preparation process of lithium-ion secondary batteries is described below:

[0036] (1) Preparation of negative electrode sheet

[0037] The negative electrode active material graphite, negative electrode conductive agent carbon microspheres, negative electrode binder SBR and CMC (mass ratio of 1:1) are mixed in a mass ratio of 90-99:1-4:0.01-10, 80-84 parts by mass of deionized water are added, and the mixture is fully stirred to obtain a negative electrode slurry; the negative electrode slurry is then evenly coated on a copper foil, and then dried, rolled, cut and other processes are performed to make a negative electrode sheet.

[0038] (2) Preparation of positive electrode sheet

[0039] After the positive electrode active material, binder and conductive agent are mixed in a certain mass ratio, NMP (N-methylpyrrolidone) is added and the mixture is fully stirred to obtain positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is made through processes such as drying, rolling and cutting.

[0040] (3) Preparation of electrolyte

[0041] In an argon atmosphere glove box with a water content of <10ppm, fully dried lithium salt (LiPF6) is dissolved in an organic solvent and mixed evenly to obtain an electrolyte, wherein the concentration of LiPF6 is 1 mol / L.

[0042] (4) Preparation of diaphragm

[0043] A 12 μm thick polypropylene (PP) or polyethylene (PE) porous polymer film is selected.

[0044] (5) Battery assembly:

[0045] The positive electrode sheet, separator and negative electrode sheet prepared above are stacked or wound in sequence to form a bare battery cell; then wrapped with aluminum plastic film, transferred to a vacuum drying oven and dried at 120°C, sealed after injecting electrolyte, and the electrolyte is formed to finally prepare a soft-pack battery (i.e., a lithium-ion secondary battery).

[0046] Those skilled in the art will understand that the above-described method for preparing the battery is only an example, and other methods commonly used in the art may be used without departing from the contents disclosed in the present application.

[0047] The reagents and raw materials used in the present invention are commercially available.

[0048] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples.

[0049] Example 1

[0050] Preparation of negative electrode

[0051] (1) Preparation of carbon microspheres

[0052] 1. MgO@C (carbon-coated magnesium oxide material) was prepared by in-situ magnesium oxide template method at 800°C.

[0053] Basic magnesium carbonate (5 g) was placed in a quartz tube in a vertical furnace and heated at 10 °C min -1 The temperature was raised to 800 °C at a rate of 50 μL min -1 300 μL of benzene was injected at a feeding rate of , and the mixture was kept warm for 1 h. The mixture was naturally cooled to room temperature in an Ar gas flow to obtain the mesostructured MgO@C.

[0054] 2. Use 6 mol L -1 HCl was used to remove MgO, and the mixture was washed with ultrapure water several times until neutral, and freeze-dried to obtain hierarchical carbon microspheres. The specific surface area of ​​the carbon microspheres was 1400 m 2 / g, the size of the carbon nanocage is 18nm, the thickness of the carbon nanosheet is ≤100nm, and the particle size of the carbon microsphere is 7μm.

[0055] Specifically, see Figure 1 , Figure 1 FIG. 1 shows a scanning electron microscope image of carbon microspheres 100 at 10K magnification. Figure 1 As can be seen from the figure, the carbon microsphere 100 is composed of sheet-like carbon nanosheets 101. Figure 2 As shown, Figure 2 shows an enlarged view of the carbon nanosheet 101, from Figure 2 As can be seen from the figure, the carbon nanosheet 101 is composed of carbon nanocages 102, and the carbon nanocages 102 have a porous three-dimensional structure. Figure 2 This is a TEM transmission image. Figure 2 It can be seen that the black edge of the carbon nano cage 102 is the grain boundary, and the gray is the transparent part, and it is gray after TEM transmission. Therefore, it can be seen that the carbon nano cage 102 is a porous three-dimensional structure. In this application, the specific surface area of ​​the carbon microsphere 100 is 1400m 2 In the present application, the carbon microsphere 100 has a large specific surface area (1400 m 2 / g), when used as a conductive agent, the conductive network formed in the electrode is more dense, and the negative electrode resistance is smaller. In addition, the carbon nano cage 102 structure inside the carbon microsphere 100 can be filled with electrolyte, which can provide more ion transmission channels during the cycle process, greatly improve the battery cycle life, and improve the electrode liquid retention capacity.

[0056] In this embodiment, the size L of the carbon nano cage 102 is 18nm, and further, the size L is the maximum size of the carbon nano cage 102 in the three-dimensional direction, that is, the size L is the length of the carbon nano cage 102. Further, the thickness H of the carbon nano sheet (petal) 101 is ≤100nm. In the present application, when the size L of the carbon nano cage 102 is in this range (10nm-20nm), the shape (such as petal shape) of the carbon nano sheet 101 composed thereof can be better, and combined with the thickness H≤100nm of the carbon nano sheet (petal) 101, the specific surface area of ​​the carbon micron ball 100 formed thereafter can be larger, thereby improving the performance of the battery. In the present application, there is space between the "petals" and the "petals", and the nano cage is a hollow structure. When the negative electrode material expands, the carbon nano ball is squeezed, which can effectively alleviate the expansion of the negative electrode plate, while absorbing the stress generated by the expansion of the negative electrode material, and improving the stability of the plate.

[0057] Return to reference Figure 1 ,from Figure 1 As can be seen from the figure, the carbon nanosheet 101 has a petal-like shape (such as Figure 1 In other words, the carbon nanosheets 101 may be petals, and the petals are aggregated to form the carbon micro-flowers of the carbon micro-spheres 100. Figure 1 ,like Figure 1 As shown, the particle size D of the carbon microsphere 101 is 7 μm. In the present application, the petal-shaped carbon nanosheets 101 are aggregated to form the carbon microflower of the carbon microsphere 100, and the particle size D of the carbon microsphere 101 is 2 μm-10 μm. In the present application, the carbon microsphere 100 is a carbon microflower, and when the particle size D of the carbon microsphere 101 is 2 μm-10 μm, the carbon microsphere 101 can be used as a conductive agent with better dispersion, so that the conductive network formed in the negative electrode plate is more dense.

[0058] (2) Preparation of negative electrode sheet

[0059] The negative electrode active material artificial graphite, the negative electrode conductive agent carbon microspheres, the negative electrode binder SBR and CMC (mass ratio of 1:1) are mixed in a mass ratio of 98:1:1, and 82 parts by mass of deionized water are added, and the mixture is fully stirred to obtain a negative electrode slurry; the negative electrode slurry is then evenly coated on a copper foil; and the negative electrode sheet is made after drying, rolling, cutting and other processes.

[0060] Example 2

[0061] The preparation method is consistent with that in Example 1, except that in Example 2, basic magnesium carbonate (5 g) is placed in a quartz tube in a vertical furnace and heated to 1000° C., 500 μL of benzene is injected, and the temperature is kept for 2 h, and then carbon microspheres are obtained, wherein the specific surface area of ​​the carbon microspheres is 1100 m 2 / g, the size of the carbon nanocage is 10nm, and the particle size of the carbon microsphere is 8μm.

[0062] Example 3

[0063] The preparation method is consistent with that in Example 1, except that in Example 3, basic magnesium carbonate (5 g) is placed in a quartz tube in a vertical furnace and heated to 1000° C., 350 μL of benzene is injected, and the temperature is kept for 3 h, and then carbon microspheres are obtained, wherein the specific surface area of ​​the carbon microspheres is 1300 m 2 / g, the size of the carbon nanocage is 15nm, and the particle size of the carbon microsphere is 6μm.

[0064] Example 4

[0065] The preparation method is consistent with that in Example 1, except that in Example 4, basic magnesium carbonate (5 g) is placed in a quartz tube in a vertical furnace and heated to 800° C., 200 μL of benzene is injected, and the temperature is kept for 1 h, and then carbon microspheres are obtained, wherein the specific surface area of ​​the carbon microspheres is 1200 m 2 / g, the size of the carbon nanocage is 10nm, and the particle size of the carbon microsphere is 2μm.

[0066] Example 5

[0067] The preparation method is consistent with that of Example 1, except that the metal salt used in Example 5 is basic zinc carbonate (5 g), wherein the specific surface area of ​​the obtained carbon microspheres is 1500 m 2 / g, the size of the carbon nanocage is 20nm, and the particle size of the carbon microsphere is 10μm.

[0068] Example 6

[0069] The preparation method is consistent with that of Example 1, except that the metal salt used in Example 6 is basic iron carbonate (5 g), wherein the specific surface area of ​​the obtained carbon microspheres is 1400 m 2 / g, the size of the carbon nanocage is 12nm, and the particle size of the carbon microsphere is 4μm.

[0070] Example 7

[0071] The preparation method is consistent with that of Example 1, except that in Example 7, the mass ratio of the negative electrode active material artificial graphite, the negative electrode conductive agent carbon microspheres, and the negative electrode binder (SBR and CMC) is 95:3:2.

[0072] Example 8

[0073] The preparation method is consistent with that of Example 1, except that in Example 8, the mass ratio of the negative electrode active material artificial graphite, the negative electrode conductive agent carbon microspheres, and the negative electrode binder (SBR and CMC) is 96:2.5:1.5.

[0074] Example 9

[0075] The preparation method is consistent with that of Example 1, except that the negative electrode active material in Example 9 is silicon carbon (5%) and artificial graphite, and the mass ratio of silicon carbon to artificial graphite is 5:95.

[0076] Example 10

[0077] The preparation method is consistent with that of Example 1, except that in Example 10, the conductive agent is carbon microspheres and acetylene black (mass ratio is 1:1), and the mass ratio of the negative electrode active material artificial graphite, the negative electrode conductive agent (carbon microspheres and acetylene black), and the negative electrode binder (SBR and CMC) is 95:3:2.

[0078] Embodiment 11

[0079] The preparation method is the same as that of Example 1, except that in Example 11, the organic carbon source is thiophene and pyridine (300 μL, mass ratio 1:1). Among them, the specific surface area of the carbon microspheres is 1400 m 2 / g, the size of the carbon nanocages is 18 nm, the thickness of the carbon nanosheets is ≤100 nm, and the particle size of the carbon microspheres is 7 μm.

[0080] Comparative Example 1

[0081] The preparation method is the same as that of Example 1, except that in Comparative Example 1, the anode active material is silicon carbide (5%) and artificial graphite, and the mass ratio of silicon carbide to artificial graphite is 5:95, and the conductive agent is acetylene black.

[0082] Comparative Example 2

[0083] The preparation method is the same as that of Example 1, except that in Comparative Example 1, the conductive agent is acetylene black.

[0084] Comparative Example 3

[0085] The preparation method is the same as that of Example 1, except that in Comparative Example 3, 5 g of basic magnesium carbonate is placed in a quartz tube in a vertical furnace and heated to 700 °C, 300 μL of benzene is injected, and the temperature is kept for 0.5 h, and then carbon microspheres are obtained. Among them, the specific surface area of the carbon microspheres is 900 m 2 / g, the size of the carbon nanocages is 7 nm, and the particle size of the carbon microspheres is 5 μm.

[0086] The testing methods for the carbon microspheres in the above Examples 1-11 and Comparative Examples 1-3 are as follows:

[0087] Specific surface area testing method: Use a specific surface area and porosity analyzer: First, degas and activate the above carbon microsphere samples at 300 °C for 6 h, and then use the volumetric method to perform adsorption measurement with N2 as the adsorbate at 77 K. The pore structure and specific surface area are measured on a Thermo Fisher Scientific Surfer Gas Adsorption Porosimeter instrument. The specific surface area is calculated by the BET (Brunauer-Emmett-Teller, 0.05 < p / p0 < 0.3) method, and the pore distribution is obtained by processing the adsorption branch isotherm data with the HK model (Horvath-Kawazoe, <2 nm micropores) and the BJH model (Barrett-Joyner-Halenda, >2 nm mesopores and macropores).

[0088] Measurement of the particle size of carbon microspheres:

[0089] Method 1: 10K magnification SEM (scanning electron microscope) image, select at least 5 areas in the SEM image, each area is about 12μm by 12μm; measure the diameter of the carbon microspheres and take the average value;

[0090] The thickness of the carbon nanosheets,

[0091] Carbon nanosheet thickness measurement: 10K magnification SEM (scanning electron microscope) image, select an area of ​​about 12μm by 12μm in the SEM image, measure the thickness of the carbon nanosheet (nano measure tool), calculate the thickness data, remove the first and last parts, and take the thickness data located in the middle section 85%, which is the thickness of the carbon nanosheet;

[0092] Nanocage Dimensions

[0093] Nanocage size determination: 10K magnification SEM (scanning electron microscope) image, select an area of ​​about 12μm by 12μm in the SEM image, measure the size of each nanocage (nano measure tool), the size of a nanocage is the distance between the two ends farthest apart, count the size data of each nanocage, remove the first and last ends, and take the size (length) data located at 85% of the middle section as the size of the nanocage.

[0094] Furthermore, the negative electrode sheets in the above-mentioned embodiments 1-11 and comparative examples 1-3 can be formed into secondary batteries by the following method.

[0095] Positive electrode sheet: After mixing the positive electrode material lithium iron phosphate (LFP), the positive electrode conductive agent SP (conductive carbon black) and the positive electrode binder PVDF (polyvinylidene fluoride) in a mass ratio of 97:2:1 (a total of 100 parts by mass), add 82 parts by mass of NMP, stir and mix thoroughly to obtain a positive electrode slurry; coat the positive electrode slurry on the positive electrode collector aluminum foil, dry, roll, cut and other processes to make a positive electrode sheet.

[0096] Electrolyte: The organic solvent in the electrolyte is a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC), wherein the weight ratio of EC, EMC and DEC is 1:1:1. The electrolyte is LiPF6, and the total content of LiPF6 is 12.5% ​​of the total weight of the electrolyte. Diaphragm: A porous membrane of PE with a thickness of 11um is used as the diaphragm (wherein the thickness of the diaphragm is 9μm to 18μm; the air permeability is 180s / 100mL to 380s / 100mL; the porosity is 30% to 50%).

[0097] Finally, the positive electrode sheet, the separator and the negative electrode sheet are sequentially placed into the mold for assembly; after assembly, the electrolyte is injected, and after formation and packaging, a lithium-ion secondary battery (soft pack, 1.2Ah) is obtained.

[0098] The secondary batteries in the above Examples 1-11 and Comparative Examples 1-3 were subjected to cycle performance tests.

[0099] Cycle performance test method: At 25°C, first charge and discharge the activated battery for one cycle at a rate of 0.1C in the operating voltage range of 2.5V (discharge cut-off voltage) to 4.2V (charge cut-off voltage), then connect the above-prepared lithium-ion battery to the Blue Electric charge and discharge tester, and then perform long-term cycling at a rate of 0.3C within the operating voltage range, and record the capacity Cn of each cycle until the ratio of the capacity of the nth cycle to the capacity of the first cycle of the 0.3C test is 90%, the capacity retention rate of the n-1th cycle is defined as 90%, the number of cycles is recorded as n-1, and the test is stopped.

[0100] Expansion force test:

[0101] The expansion force test method is determined by testing the battery cell. Specifically, the expansion force of the battery cell with LFP (lithium iron phosphate) positive electrode material is tested by a pressure sensor. The pressure sensor is fixed to the battery cell. During the charging and discharging process, the battery cell expands and the pressure sensor is compressed, thereby testing the expansion force of the battery cell. During this period, since the expansion of the LFP positive electrode sheet can be ignored, the expansion force of the negative electrode can be obtained through the expansion force of the battery cell with LFP positive electrode material.

[0102] The test results are shown in Table 1 below.

[0103]

[0104]

[0105]

[0106] See the above Example 1 and Comparative Example 1 and the following Figure 3 and Figure 4 , Figure 3 The capacity retention rates of Example 1 and Comparative Example 1 are shown respectively, and Figure 4 The capacity retention rates of Example 2 and Comparative Example 2 are shown. Figure 3 and Figure 4It can be seen that by using the carbon microspheres prepared in the present application as a conductive agent, the expansion force of the secondary battery can be significantly improved, and the improvement effect relative to the silicon-carbon negative electrode battery is more significant. Relative to Comparative Examples 1-2, the cycle expansion force of the battery of Example 1-2 has been greatly reduced. This is because there is space between the carbon nanosheets of the carbon microspheres, and the nanocage is a hollow structure. When the negative electrode material expands, the carbon nanospheres are squeezed, which can effectively alleviate the expansion of the pole piece, and absorb the stress generated by the expansion of the negative electrode material, thereby improving the stability of the pole piece. In addition, the present application uses carbon microspheres as a conductive agent. When the amount is the same as that of ordinary conductive agents (acetylene black), the conductive network formed in the pole piece is denser and the resistance of the negative pole piece is smaller. In addition, the carbon nanocage structure inside the carbon microsphere can be filled with electrolyte, which can provide more ion transmission channels during the cycle process, greatly improving the battery cycle life. Reducing the expansion force is beneficial to the structural stability of the pole piece and the battery, and the safety of the battery cell structure strength is better, which can effectively reduce the problems such as shell cracking caused by the large stress generated by the expansion of the battery cell.

[0107] From Examples 2-6 and Comparative Example 3, it can be seen that the specific surface area of ​​carbon microspheres is 1100m 2 / g or above, optionally between 1100-1500m 2 / g, the size of the carbon nano cage is between 10nm-20nm and the particle size of the carbon micron ball is between 2μm-10μm, and the mass fraction of the conductive agent is 0.01%-10% based on the total mass of the negative electrode plate, when used as the conductive agent of the negative electrode plate, the cycle life of the corresponding battery can be improved. Comparing Examples 2-6 with Comparative Example 3, it can be seen that the specific surface area of ​​the carbon micron ball is less than 1100m 2 / g, the cycle performance of the battery is significantly reduced. In addition, it can be seen from Examples 5-6 that the use of metal salts including magnesium carbonate, zinc carbonate and iron carbonate can form carbon microspheres with a high specific surface area.

[0108] It can be seen from Examples 7-8 that based on the total mass of the negative electrode plate, the mass fraction of the negative electrode active material is 90%-99% (optionally 95%-98%), the mass fraction of the binder is 1%-4%, and the mass fraction of the conductive agent is 0.01%-10% (optionally 0.01%-1%). In the present application, carbon microspheres are used instead of traditional conductive carbon to act as an electronic conductive network, which can effectively improve the performance of the negative electrode plate. Furthermore, there is space between the carbon nanosheets of the carbon microspheres, and the nanocage is a hollow structure. When the negative electrode material expands, the carbon nanospheres are squeezed, which can effectively alleviate the expansion of the plate, while absorbing the stress generated by the expansion of the negative electrode material, thereby improving the stability of the plate.

[0109] It can be seen from Example 9 that the negative electrode active material of the negative electrode plate can include silicon carbon and artificial graphite. It can be seen from Example 10 that when the conductive agent includes carbon microspheres, other conductive agents (acetylene black) can be added without affecting the cycle life of the battery.

[0110] In addition, it can be seen from Examples 1 and 11 that the organic carbon source for preparing carbon microspheres can include one or more of benzene, thiophene (carbon with S added), pyridine (carbon doped with N), xylene and pyrimidine, and all of them can obtain carbon microspheres with a large specific surface area (≥1100m 2 / g) of carbon microspheres.

[0111] The features of several embodiments are summarized above so that those skilled in the art can better understand aspects of the present invention. Those skilled in the art should understand that they can easily use the present invention as a basis to design or modify other processes and structures for implementing the same purpose and / or achieving the same advantages as the embodiments introduced herein. Those skilled in the art should also appreciate that this equivalent construction does not deviate from the spirit and scope of the present invention, and that they can make multiple changes, substitutions and changes herein without departing from the spirit and scope of the present invention.

Claims

1. A negative electrode plate, characterized in that: include: Negative electrode active material, binder and conductive agent, Wherein, the conductive agent comprises carbon microspheres, the carbon microspheres are composed of layered carbon nanosheets, the carbon nanosheets are composed of carbon nanocages, and the carbon nanocages have a porous three-dimensional structure.

2. The negative electrode sheet according to claim 1, characterized in that: The specific surface area of ​​the carbon microspheres is ≥1100m 2 / g.

3. The negative electrode sheet according to claim 1, characterized in that: The length of the carbon nano cage is 10nm-20nm.

4. The negative electrode sheet according to claim 1, characterized in that: The carbon nanosheets have a petal shape formed by agglomeration of carbon nanocages, and the carbon microspheres are carbon microflowers formed by carbon nanosheets.

5. The negative electrode sheet according to claim 1, characterized in that: The thickness of the carbon nanosheet is ≤100 nm.

6. The negative electrode sheet according to claim 1, characterized in that: The particle size of the carbon microspheres is 2 μm-10 μm.

7. The negative electrode sheet according to claim 1, characterized in that: Based on the total mass of the negative electrode plate, the mass fraction of the negative electrode active material is 90%-99%, the mass fraction of the binder is 1%-4%, and the mass fraction of the conductive agent is 0.01%-10%.

8. A method for preparing carbon microspheres as a conductive agent for negative electrode sheets according to any one of claims 1 to 7, characterized in that: include: heating the metal salt to above a first temperature in an inert atmosphere; adding an organic carbon source and keeping the temperature for a first time to obtain a carbon-coated metal oxide; as well as removing the metal oxide to obtain the carbon microspheres, Wherein, the first temperature is 800°C±50°C.

9. The method according to claim 8, characterized in that The metal salt comprises one or more of magnesium carbonate, zinc carbonate and iron carbonate, and the organic carbon source comprises one or more of benzene, thiophene, pyridine, xylene and pyrimidine; and / or The first time is more than 1 hour; and / or The amount of the organic carbon source added relative to the metal salt is 40 μL / g-100 μL / g.

10. A secondary battery, characterized in that: include: A negative electrode plate, wherein the negative electrode plate is the negative electrode plate according to any one of claims 1 to 7.

11. An electrical device, characterized in that: The secondary battery according to claim 10 is included.

Citation Information

Patent Citations

  • Lithium battery cathode material, lithium battery cathode, preparation method of lithium battery cathode, and lithium battery

    CN107742727A

  • Negative electrode slurry

    CN108511754A

  • A high-energy silicon-containing lithium battery and a preparation method thereof-

    CN109244386A

  • Porous three-dimensional composite material based on carbon nanosheets

    CN110247027A

  • Preparation method of mesostructure carbon-based nanocage for high-performance supercapacitor

    CN114141548A